Genome-wide analysis of the Populus trichocarpa laccase gene family and functional identification of PtrLAC23 - Liao, Boyang; Wang, Chencan; Li, Xiaoxu; Man, Yi; Ruan, Hang; Zhao, Yuanyuan (Frontiers in Plant Science, 2023)
Biofuel is a kind of sustainable, renewable and environment friendly energy. Lignocellulose from the stems of woody plants is the main raw material for “second generation biofuels”. Lignin content limits fermentation yield and is therefore a major obstacle in biofuel production. Plant laccase plays an important role in the final step of lignin formation, which provides a new strategy for us to obtain ideal biofuels by regulating the expression of laccase genes to directly gain the desired lignin content or change the composition of lignin. Here, a comprehensive analysis of the P. trichocarpa laccase gene (PtrLAC) family was performed. Some ancient PtrLAC genes were identified by gene duplication analysis, interspecific collinearity analysis and phylogenetic analysis. Gene structure and distribution of conserved motifs clearly showed sequence characteristics of each PtrLAC. Combining published RNA-Seq data and real-time quantitative PCR (qRT-PCR) analysis, we revealed the expression pattern of PtrLAC gene family. Prediction results of cis-acting elements show that PtrLAC gene regulation was closely related to light. Through above analyses, we selected 5 laccases to simulate protein 3D structures by using Alphafold2 and found that PtrLAC23 may be closely related to the lignification. Fluorescence observation of proLAC23::LAC23-EGFP transgenic Populus stem transects confirmed the structural simulation results. Together, these findings not only provide new insights into the characteristics and functions of Populus laccase, but also give a new understanding of the broad prospects of plant laccase in lignocellulosic biofuel production.